PERFORMANCES OF BROILER CHICKEN FED RATIONS CONTAINNING CINNAMON BARK POWDER (Cinnamomum burmannii). - Tangkere, Evacuree S.; Lawani, Anastasya A.; Leke, Jein R; Sompie, Florencia N. (PT. Jurnal Center Indonesia Publisher, 2025)
This research was conducted in order to determine or to re-examine the performances of broiler chickens fed ration containing cinnamon bark powder (Cinnamomum burmannii). Eighty of CP 707 broiler chickens aged of 2 weeks were used and kept until 6 weeks old. Completely Randomized Design with 5 treatments and 4 replications each treatment was used in this study; the treatments used were, T0= 100% basal ration without cinnamon bark powder (CBP), T1= 99.5% basal ration + 0.5% CBP, T2= 99% basal ration + 1% CBP, T3= 98.5% basal ration + 1.5 % CBP, and T4= 98% basal ration + 2% CBP. The measurements taken were feed consumption, weight gain, feed conversion, and final body weight. The results of analysis of variance (ANOVA) and Duncan test showed that, giving cinnamon bark powder up to 2% in the ration had an effect on CP 707 broiler chickens aged 2-6 weeks; had a very significantly different effect (P<0.01) on body weight gained and so, on final body weight; and significantly different (P <0.05) on feed conversion, but not on feed consumption. In this study, the higher the level of CBP in the ration, the weight gained and final body weight decreased but feed conversion increased. Based on the results of the analysis and discussion, it can be concluded that giving cinnamon bark powder as a natural feed additive up to 2% in the feed did not improve the performance of CP 707 broiler chickens, because of weight gained and final body weight of the chickens decreased, while, feed conversion increased, which means that, economically it was not getting better.